Early Life Exposure to Violence: Developmental Consequences on Brain and Behavior - Mueller, Isabelle; Tronick, Ed (Frontiers in Behavioral Neuroscience, 2019)
Exposure to intimate partner violence (IPV) can have long-lasting effects on a child's socio-emotional and neurological development. Research has focused on the effects of IPV on women or older children, while the developmental consequences of exposure to domestic violence during early childhood are less well documented. However, one would expect significant developmental effects since the infant's brain and stress-related systems are especially susceptible to environmental stimuli. The goal of this mini-review is to examine how findings on infant exposure to IPV can be related to risk and resilience of development in infancy. We describe the known effects of witnessing violence during the perinatal period on socio-emotional development and the possible pathways by which IPV affects brain and stress-regulating systems. Exposure to IPV during infancy disrupts the infant's emotional and cognitive development, the development of the HPA axis and brain structures related to witnessing itself (auditory and visual cortex). The findings are embedded in the context of the resource depletion hypothesis. A central problem is the dearth of research on exposure to IPV during infancy, its effect on caregiving, and infant development. Nonetheless the available evidence makes it clear that policies for prevention of IPV are critically needed.